Portable pulse X-ray apparatus with gas insulation - Avilov, E.A.; Baltakov, A.Y.; Zavyalov, N.V.; Kanunov, I.M.; Polienko, G.A.; Punin, V.T.; Khoroshailo, E.S.; Yuriev, A.L. (Вопросы атомной науки и техники, 2001)
There are presented the data on development, investigation and application of a pulse X‑ray apparatus with gas insulation. There are described circuit and design solutions for a 90 kV apparatus to be used in medical X-ray diagnostics and a 200 kV apparatus to be applied for the researches of high-speed processes. There are demonstrated the advantages of using gas under pressure as insulating medium. There are presented basic output characteristics of the devices.